The Effectiveness of Breaststroke Swimming Training Models and Swimming Style Variation Methods at the ESC Swimming Club (Embrio Swimming Club) - Selfia Berlian; Dicky Reva Apriana Sanga Dwi (Jurnal Pendidikan Jasmani (JPJ), 2026)
This study aims to determine the effectiveness of the breaststroke swimming training model using the variation method for athletes at the ESC Swimming Club (Embrio Swimming Club). The background of the study is based on the finding that many athletes have difficulty mastering breaststroke techniques, especially the coordination of hand, leg, and breathing movements, due to monotonous conventional training methods. The research method used was an experiment with a one-group pretest-posttest design. The research sample consisted of 10 athletes selected using a purposive sampling technique. The treatment in the form of a variation training model was given for six meetings in two weeks, including training on land using resistance loop bands and training in water using a pullboy. The research instrument was a breaststroke swimming skills test covering five aspects: gliding, leg movement, hand movement, breathing, and coordination. The results of the analysis showed an increase in the average score from 51.50 in the pretest to 85.00 in the posttest. Normality and homogeneity tests showed that the data were normally distributed and homogeneous. The paired sample t-test produced a significance value of 0.0001 (<0.05), so it can be concluded that there was a significant difference between the results before and after the treatment. This proves that the swimming style variation training model is effective in improving breaststroke technique skills. Implementing this method can be an alternative strategy for coaches to optimize athlete performance, reduce boredom, and motivate athletes during training.